Study of Recurrent Laryngeal Nerve Paralysis Following Thyroidectomy (Bangladesh Journal of Otorhinolaryngology, 2019)
Abstract not availableBangladesh J of Otorhinolaryngology; October 2018; 24(2): 162-166